2015
DOI: 10.5367/te.2014.0377
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Quality of Government and Tourism Destination Competitiveness

Abstract: This paper examines the impacts of the quality of government on international tourism competitiveness. Quality of government is conceptualized in terms of an absence of corruption, a well-established rule of law and bureaucratic efficiency. Based on the cross-country analysis of the Travel & Tourism Competitiveness Index (World Economic Forum, 2013), the main finding of the study demonstrates that quality of government is positively associated with tourism competitiveness and that this positive effect remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 17 publications
3
31
2
1
Order By: Relevance
“…A time-series analysis conducted on Malaysian tourism by Tang [23] showed that international tourists are concerned about the political stability, law enforcement, government effectiveness, and regulations of the country [24]. Efficient governance and institutions stimulate economic growth and encourage tourism and suggest further that improvement in institutional performance stimulates economic growth and signals the level of security, which may increase tourism demand [6,25,26]. In addition, better control of corruption and stability is highly likely to attract more tourism demand [27][28][29].…”
Section: Brief Literature Review On Institutional Quality and Tourismmentioning
confidence: 99%
“…A time-series analysis conducted on Malaysian tourism by Tang [23] showed that international tourists are concerned about the political stability, law enforcement, government effectiveness, and regulations of the country [24]. Efficient governance and institutions stimulate economic growth and encourage tourism and suggest further that improvement in institutional performance stimulates economic growth and signals the level of security, which may increase tourism demand [6,25,26]. In addition, better control of corruption and stability is highly likely to attract more tourism demand [27][28][29].…”
Section: Brief Literature Review On Institutional Quality and Tourismmentioning
confidence: 99%
“…The relationship between tourism and quality of the institutions of the societies where it is developed has, hitherto, been little studied. In addition, this limited research explores such relationships only partially or indirectly (Das and Di Renzo, 2010;Brau et al, 2011;Lee, 2015;Poprawe, 2015). The specific links that can be established between the two issues remain uncertain.…”
Section: Literature Review and Theoretical Argumentsmentioning
confidence: 99%
“…The specific links that can be established between the two issues remain uncertain. Lee (2015) employs a cross-country regression analysis of 117 countries and finds that quality of government is positively associated with international tourism competitiveness (Travel and Tourism Competitiveness Index). Furthermore, this study concluded that the positive effect of quality of government is independent from the effect of democracy.…”
Section: Literature Review and Theoretical Argumentsmentioning
confidence: 99%
See 2 more Smart Citations